Traversal of arbitrary sequences of UCM symbolic transitions for test generation - Guba, A.A. (Інститут програмних систем НАН України, 2025)
The paper proposes a method of traversal of high-level multi-threaded models formalized in UCM language. The pros and cons of this approach comparing to the existing ones are considered. The method that allows state space exploring of UCM models using symbolic solving and proving is presented. The generation of symbolic traces used for software system testing is described.Prombles in programming 2014; 2-3: 107-111